AI and Telecommunication Privacy: Rethinking Legal Protections against Algorithmic Surveillance - Inam Ul Mansoor, Sheikh (Law, State and Telecommunications Review, 2025)
[Purpose] This paper explores how artificial intelligence (AI) can aid in the integration of telecommunication networks, and how it will affect privacy. It talks about the threats that AI brings to consumer privacy, such as algorithmic monitors that are challenging and explain what does and doesn’t seem to be working to protect consumer privacy in present legislation. The purpose is to study the integration of AI and telecommunication data privacy to find that there is a need to have new set of laws and weighty privacy protection in this age of digital transformation. [Methodology/approach/design] The paper critically analyses historical interactions of AI with telecommunication privacy, discusses how existing policies work and what gaps exist in current legislation. Examining the validity of such risks in telecommunication networks when it comes to privacy violation, data exploitation, and the need for clear regulations of the system. Moreover, the methodology proposes an interdisciplinary approach comprised of legal, technological, and ethical stakeholders to handle the problems in question. [Findings] And finally, the paper concludes that the existing legal frameworks cannot secure privacy of consumer in the framework of AI-based telecommunication systems. That is why it emphasizes the need for international privacy standards, independent audits and robust national regulatory bodies. It calls for new legal guidelines that would guarantee transparency, responsibility and consumer consent as well as foster collaboration among the different stakeholders to improve privacy protection and data control in AI systems. [Practical implications] The paper parallels strong privacy protections and ethical practices of AI in telecommunication systems. It calls for new legal and international standards of privacy. The intention behind these recommendations is to maintain the privacy and control of the consumer’s data within AI powered systems. [Originality/value] Finally, this research uniquely combines legal, technological, and ethical aspects of litigation involving AI and privacy in telecommunications all into one. It draws the gaps in the existing laws and provides innovative solutions for privacy protection. The modern concern addressed by the paper is privacy, and the value of the paper is in the interdisciplinary approach it uses to address that specific concern.